2017
DOI: 10.1002/pbc.26677
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine‐induced neuropathy in pediatric patients with acute lymphoblastic leukemia in Oman: Frequent autonomic and more severe cranial nerve involvement

Abstract: Peripheral neuropathy was the commonest form of VCR-related neuropathy. Autonomic neuropathy was relatively common in our patients. Cranial neuropathy is a serious side effect of VCR that can be severe, involving multiple cranial nerves and needs prompt recognition and management. Concomitant administration of pyridoxine and pyridostigmine does not seem to protect against further neurological damage in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 30 publications
6
43
0
Order By: Relevance
“…Peripheral (motor, sensory) neuropathies are common, usually caused by vincristine, and are basically completely reversible, but may require many months to improve (4). The study published by Nazir (14) reported that 19 out of 103 pediatric patients developed VCR-related neuropathy. Clinical symptoms started after 2-11 doses of VCR.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral (motor, sensory) neuropathies are common, usually caused by vincristine, and are basically completely reversible, but may require many months to improve (4). The study published by Nazir (14) reported that 19 out of 103 pediatric patients developed VCR-related neuropathy. Clinical symptoms started after 2-11 doses of VCR.…”
Section: Discussionmentioning
confidence: 99%
“…59 Sjögren's syndrome, 50 vitamin B6 toxicity, 18 cisplatinum toxicity 60 ) Sensory CIDP 61 Abbreviations: CIDP, chronic inflammatory demyelinating polyradiculoneuropathy; HIV, human immunodeficiency virus. 63 heavy metals, organic solvents, acrylamide, 64 cisplatin, 60 vincristine, 65 paclitaxel, 66…”
Section: Leukemiamentioning
confidence: 99%
“…Vincristine neuropathy 65 Abbreviations: HIV, human immunodeficiency virus; HSAN, hereditary sensory and autonomic neuropathy. sensory neuropathy will have normal motor NCS, the loss of sensory feedback will often lead to a sense of weakness or abnormal motor function.…”
Section: Leprosy 27 )mentioning
confidence: 99%
“…Peripheral neuropathy is a common adverse effect of vincristine. Peripheral neuropathy can affect motor, sensory, and autonomic peripheral nerve fibers 2,3 Rarely cranial nerves are involved. 3 Neuropathy is reported in 3 to 93% children treated with vincristine.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral neuropathy can affect motor, sensory, and autonomic peripheral nerve fibers 2,3 Rarely cranial nerves are involved. 3 Neuropathy is reported in 3 to 93% children treated with vincristine. 3,4 Symmetrical motor axonal polyneuropathy is the most common pattern of involvement seen with vincristine.…”
Section: Introductionmentioning
confidence: 99%